An analysis of bunker design and construction’s impact on golf course management - Soldan, Daryn M. (Kansas State University, 2009)
Sand bunkers serve multiple roles as components in the game of golf and golf course design. Bunkers began on early Scottish linksland courses as natural areas of exposed sand. However, as golf has grown since those early beginnings centuries ago, bunkers have become designed, constructed and maintained elements of the course. Significant resources are now used to build and maintain bunkers, in some cases more than are used on greens. As economic factors cause those in the golf business to search for opportunities to be more efficient, bunker maintenance and management plays a key role. This study identifies and analyzes the factors that are most important to bunker design, maintenance and management. It also examines the bunker design – management relationship and the impacts that bunker design decisions have on golf course management. A survey questionnaire targeted toward golf course designers and golf course superintendents was used to obtain opinions and statistical data pertaining to the study. A total of 109 completed surveys were returned. Survey responses were used to determine: 1. The importance of bunkers 2. Bunkers’ roles and characteristics 3. The most important factors related to bunker design and maintenance 4. The reasoning behind undertaking bunker modification projects 5. The degree of involvement among parties involved in bunker design and construction. Additional analysis was undertaken to determine potentially important differences or disconnects between the responses of the two survey groups – golf course architects and superintendents. Survey results and analysis indicate that the primary roles of bunkers are intended for player strategy and course aesthetics. The most important factors in bunker design and construction are their; location, visual appearance, drainage and structural quality, all of which directly impact a bunker’s overall maintainability. The results of the study and literature review show that the bunker design – management relationship appears to play a significant role in the playability and continued quality of bunkers over the long term. Issues that arise related to bunker maintenance and management can often be traced back to less than thoughtful decisions or actions made during design and construction. Conclusions are also presented regarding limitations of the study and potential areas for future related research. Additional exploration regarding the specifics of bunker design, construction and maintenance, as well as the associated resource expenditures, would be of relevance to professionals practicing in golf course architecture and maintenance. Future research also might focus on golf course components beyond bunkers using methodology similar to that set forth in this study.
Keywords: Golf course architecture; Golf; Maintenance; Management; Bunkers; Landscape Architecture; Landscape Architecture (0390)